A experiência do sujeito migrante no mundo contemporâneo - uma leitura de Estive em Lisboa e lembrei de você, de Luiz Ruffato - Oliveira, Carolina (2014)
The present work aimes to accomplish a critical approach of Estive em Lisboa e lembrei de você, with purpose of focusing on the instigating fictional game proposed by the novel. Situated on the fictional production oh the author, Estive em Lisboa e lembrei de você represents his first title in which the story focuses exclusively in the existential trajectory o fone individual, knowing that until the moment his narratives are constituted by painels, in which social groups or communities are represented by relates subjectivity networks, composing the story. In this sense, the fictional game established by the novel whereby is introduced another voice tha permeates the narrator‟s speech, reveals the way whereby the narratorprotagonist experience acquires a more ample meaning evincing that the value contained in such life trajectory transcends the borders of the novel‟s hero individual experience. In the attempt of perceiving how this extention of meaning happens, we analysze the recall performed by the narrator-protagonist, the interferences of the other voice evident during the narrator‟s speech and the narrative parlance explored by the novel. Indicated the realistic proposal of Luiz Ruffato‟s novel, we believe to be bringing to the surface of this work the fictional artífices whereby was built the relation between the point of view of the narrator-protagonista and the point of view of the other voice that permeates the narrative, whose interlace resulted in the representation of the migrant subject‟s experience in the contemporary world.